Surgical and Conservative Treatment of Post-infarction Left Ventricular Pseudoaneurysm - Zhong, Zhaoji; Song, Wu; Zheng, Shanshan; Liu, Sheng (Frontiers in Cardiovascular Medicine, 2022)
Background. Postinfarction left ventricular (LV) pseudoaneurysm is a rare mechanic complication of myocardial infarction and carries a substantial risk of sudden rupture. The purpose of this study is to determine the surgical results of postinfarction LV pseudoaneurysm, in comparison with conservative treatment. Methods. From 2016 to 2021, 22 consecutive patients were hospitalized for LV pseudoaneurysm, including 17 cases (77.3%) caused by myocardial infarction. Of the 17 patents, 10 (58.8%) underwent surgical repair while 7 (41.2%) was treatment medically. Clinical course, echocardiography data and surgical outcomes were analyzed. The survival of surgical group and conservative group was compared. Results. There was no peri-operative death. Intra-aortic balloon pumping (IABP) support was required in 2 (20%) patients. There was also no follow-up mortality in the surgical group. At last follow-up, all patients were NYHA I II. In the conservative group, there was one (14.3%) hospital death and two (28.6%) additional deaths during follow-up. Significant difference was found in survival between the two groups (P=0.024). Conclusions. Surgical repair of postinfarction LV pseudoaneurysm can be performed with satisfying results, while conservative treatment carries significant risk of sudden death. Surgical repair is indicated for every patient diagnosed, even for those with small pseudoaneurysm without symptoms.